PEMANFAATAN PENCAMPURAN GYPSUM DENGAN KALSIUM OKSIDA SEBAGAI ZAT ADITIF PADA SISTEM PEMBUMIAN - Dian Puspita Sukma Dewi, Ni Wayan; Janardana, I Gusti Ngurah; Arta Wijaya, Wayan (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUM, 2021)
One of the most influential factors on the grounding system is the type of soil. Each soil has a different resistivity. So, it is necessary to add media in the form of additives, one of which is a mixture of gypsum (CaSO4`.2H2O) and Calcium Oxide (CaO). The purpose of this research was to obtain the percentage of the mixture and the effectiveness between gypsum (CaSO4.2H2O) and calcium oxide (CaO) to obtain the maximum quantity of water and to decide the impact of a mixture of gypsum (CaSO4.2H2O) with calcium oxide (CaO) as a medium for additives. to reduce the resistivity of the soil. The method used in this study is an experimental research method. The results of this study showed that the mixture of gypsum and calcium oxide that was effectively used was a mixture with a ratio of 3 kg of gypsum and 1 kg of calcium oxide and the percentage decreased resistance value was 37.93%